Optimal CC-CV charging of lithium-ion battery for charge equalization controller - Hoque M.M.; Hannan M.A.; Mohamed A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Controllers; DC-DC converters; Electric batteries; Electric inverters; Electric machine control; Electric vehicles; Equalizers; Ions; Lithium; Lithium alloys; Optimization; Particle swarm optimization (PSO); Secondary batteries; Static random access storage; Systems engineering; Charge equalization; Charging control; Charging techniques; Constant current; Energy storage applications; Particle swarm optimization algorithm; PI controller parameters; Vehicle development; Lithium-ion batteries